Impact of focused wave groups on pier structures: a case study of severe breaking waves at Pont del Petroli during storm Gloria - Altomare, Corrado; Gironella, Xavier; Marzeddu, Andrea; Viñes Recasens, Manuel; Mösso, Cesar; Sospedra, Joaquim (Frontiers in Built Environment, 2024)
In January 2020, the footbridge linking the seaward platform of the Pont del Petroli pier and Badalona beach collapsed due to the sea storm so-called Gloria. Approximately 15 meters of the footbridge fell into the sea due to long-lasting wave action and strong impacts. To comprehend the intricate interplay of waves and structures that caused the pier to collapse during Gloria, a composite modelling approach was developed. The loads on each pier element were initially evaluated using the meshless DualSPHysics code, which implements the Smoothed Particle Hydrodynamics method. This evaluation was performed under severe wave conditions similar to those encountered during the storm. Numerical models were used to design an experimental campaign at the Maritime Engineering Laboratory of Universitat Polit ècnica de Catalunya -BarcelonaTech in Barcelona, Spain, using the CIEM large-scale wave flume facility. Following the sea storm Gloria, bathymetric surveys revealed significant changes in the seabed profile near the affected infrastructure zone, including sedimentary deposition and a reduction in water depth from 10m to 8m. As a result, it was anticipated that wave transformation and breaking in the vicinity of the structure would be significantly impacted. To investigate this phenomenon, various extreme wave impacts were simulated experimentally using focused wave groups. The findings of the physical model have revealed the forces that the pier was subjected to during the storm Gloria. The results suggest that wave phases have an impact on individual waves, with waves biased and asymmetric experiencing higher peaks than those focused on the crest.